Congenital anomalies following antenatal exposure to dolutegravir: a Canadian surveillance study. (3rd July 2019) - Money, D; Lee, T; O'Brien, C; Brophy, J; Bitnun, A; Kakkar, F; Boucoiran, I; Alimenti, A; Vaudry, W; Singer, J; Sauve, LJ; ,
Abstract : Objective: Dolutegravir is recommended worldwide as a first‐line antiretroviral therapy (ART) for individuals living with HIV. A recent study reported increased rates of neural tube defects in infants of dolutegravir‐treated women. This study examined rates of congenital anomalies in infants born to women living with HIV (WLWH) in Canada. Design: The Canadian Perinatal HIV Surveillance Programme captures surveillance data on pregnant WLWH and their babies and was analysed to examine the incidence of congenital anomalies. Setting: Paediatric HIV clinics. Population: Live‐born infants born in Canada to WLWH between 2007 and 2017. Methods: Data on mother–infant pairs, including maternal ART use at conception and during pregnancy, are collected by participating sites. Main outcome measures: Congenital anomalies. Results: Of the 2423 WLWH, 85 (3.5%, 95% CI 2.85–4.36%) had non‐chromosomal congenital anomalies. There was no evidence of a significant difference in rates of congenital anomalies between women who were on ART in their first trimester (3.9%, CI 1.7–7.6%) or later in the pregnancy (3.9%, 95% CI 2.6–5.6%). Four of the 80 (5.0%, 95% CI 1.4–12.3%) neonates born to WLWH on dolutegravir during the first trimester had congenital anomalies, none were neural tube defects (95% CI 0.00–3.10%). Conclusion: Despite recent evidence raising a safety concern, this analysis found no signal for increased congenital anomalies. Tweetable abstract: Five percent of the infants of Canadian women living with HIV on dolutegravir at conception had congenital anomalies; none had neural tube defects. Tweetable abstract: Five percent of the infants of Canadian women living with HIV on dolutegravir at conception had congenital anomalies; none had neural tube defects.